Amalia Schoppe e a emigração alemã para o Brasil no conto "Die Auswanderer nach Brasilien oder die Hütte am Gigitonhonha" - Neumann, Gerson R. (Contingentia, 2008)
German immigration to Brazil starts in the 19th century. In Brazil, the German Immigration Literature has already been a subject of many studies. Nevertheless, what was produced in Germany during the period of the great emigration by the land people of these emigrates is still unknown by the Brazilian people and also by the German folk. This article shows the results of a careful bibliographic research, that was made in German libraries and archives. In this article there is an important work: one narrative from Amalia Schoppe, Die Auswanderer nach Brasilien oder die Hütte am Gigitonhonha. They present interesting aspects about Brazil and about Germany at the e(im)migation context in the 19th century.